Strengthening Clean and Healthy Living Behavior Through the Establishment of a Waste Disposal System in Rural Area - Dewi Setya Paramitha; Muhammad Noor Rezki; Herni Safitri; Aulia’ul Jannah; Akhmad Parhan Naja; Ari Suprianto; Chairunnisa Suswelanda Putri; Muhammad Shaufi; Muna Linda; Nor Khairunisa (UMBanjarmasin, 2022)
Garbage is one of the main problems that until now has not been able to be handled sustainably by the Indonesian government. Garbage disposal that is not handled properly will cause big problems. This program aims to revitalize proper waste disposal and transportation at rural area. The method used by community service. The implementation was by provided trash containers in several locations and established waste management teams. The results obtained from the program are the availability of sufficient waste containers in several village locations, waste transportation was carried out at least once every 3 days using garbage carts, there are sufficient waste selection officers at temporary garbage collection and use personal protective equipment, and routine waste transportation to the landfill. It is recommended that the waste management system in Indonesia be based on community participation and not only rely on landfill. Education about waste for rural communities about reduce, reuse and recycle (3R) must always be carried out so that the waste problem can be resolved.